Possíveis reflexos da reforma tributária na arrecadação e no equilíbrio fiscal municipal: percepções dos contadores gaúchos à luz da Teoria da Difusão da Inovação - Santos, Andréia Machado dos (2025)
Tax reform is a central theme in the Brazilian fiscal landscape and profoundly affects revenue collection mechanisms and fiscal balance at different levels of government. The new tax reform in Brazil was enacted through Constitutional Amendment No. 132/2023 and is currently under regulation. In this context, the present study aimed to analyze, through the lens of the Diffusion of Innovation Theory (DIT), the perceptions of municipal accountants in Rio Grande do Sul regarding the possible effects of the new tax reform on revenue collection and fiscal balance. The theoretical framework covered the historical evolution of the Brazilian tax system, highlighting the changes introduced by the 2023 reform, literature related to tax reforms in Brazil and abroad, and the principles of DIT, which examines how innovations are perceived and adopted in different contexts. Methodologically, the research is classified as qualitative, exploratory, documentary, and survey based. Data collection occurred in two distinct ways. Initially, a documentary analysis was conducted on the transparency portals of the researched municipalities. These sources provided information on municipal revenue collection during 2021, 2022, and 2023. Subsequently, accountants from the selected municipalities participated in semi-structured interviews. The exams employed content analysis, with results triangulated for greater robustness. The main findings indicate that the relative advantage of the reform lies in tax simplification and system modernization. In the compatibility category, concerns and uncertainties were observed regarding the municipalities' ability to maintain the same level of revenue and fiscal autonomy. Regarding complexity, challenges were identified in transitioning and implementing the tax reform. In the experimentation category, concerns arose about the absence of testing processes. Furthermore, in the observability category, results remain limited, as the reform is still in its initial implementation phase. However, there are expectations that transparency and centralized revenue control, primarily by the federal government, will bring observable benefits in terms of tax justice, efficiency, and administrative simplification. Finally, the triangulation revealed that, despite the potential of the tax reform to promote fiscal justice, efficiency, and transparency, its initial acceptance is limited by challenges such as high complexity, low compatibility with the municipal reality, and the absence of experimentability, highlighting the need for mitigation strategies for its effective implementation. The main conclusion of the study is that, although the reform has the potential to simplify the system and promote greater transparency, its effectiveness depends on careful regulation and adaptive strategies that address municipal specificities. Thus, the dissertation contributes by expanding the application of DIT in the study of fiscal policies and providing support for public managers and accountants to tackle implementation challenges, fostering greater social acceptance and administrative efficiency.